Asian Century... on a Knife-edge A 360 Degree Analysis of Asia's Recent Economic Development - West, John (Springer Nature, 2018)
Asian Century; Asia's middle class; Urbanisation in Asia; Asian demographic challenges; Democracy and politics in Asia; Asia's global value chains; Economic crime in Asia; Power transition in Asia; China and US rivalry; Inclusive growth in Asia